Effect of biologics on depressive symptoms in patients with psoriasis: a systematic review. (10th December 2014) - Fleming, P.; Roubille, C.; Richer, V.; Starnino, T.; McCourt, C.; McFarlane, A.; Siu, S.; Kraft, J.; Lynde, C.; Pope, J.E.; Keeling, S.; Dutz, J.; et al.
Abstract Background Twenty to fifty percent of patients with psoriasis have depressive symptoms. Objective To describe the effects of biologics (tumour necrosis factor inhibitors [TNFi] or interleukin 12/23 inhibitors [IL‐12/23i]) on depressive symptoms in patients with psoriasis. Methods Electronic databases were searched for randomized controlled trials (RCTs) examining the effects of biologics on depressive symptoms in adults with psoriasis. Results Of the 305 publications identified, three RCTs were included in a systematic review. In a trial evaluating ustekinumab, mean change in Hospital and Anxiety Depression Rating Scale at 24 weeks from baseline was 3.1 with ustekinumab (P < 0.001) vs. 0.21 with placebo (not significant). In a trial evaluating adalimumab, mean change in Zung Self‐Rating Depression Scale at 12 weeks from baseline was −6.7 with adalimumab vs. −1.5 with placebo. In a trial evaluating etanercept, the between‐group difference at 12 weeks in Beck Depression Inventory Scale was 1.8 (95% CI: 0.6, 2.90) in favour of etanercept over placebo. Limitations are that diagnostic criteria for depression were not used and scales and data from individual RCTs could not be combined. Conclusion Adalimumab, etanercept and ustekinumab were associated with statistically significant reductions in depressive symptom scores using various scales in patients with moderate‐to‐severe psoriasis.